Jak zapewnić uczniowi niepełnosprawnemu intelektualnie w stopniu lekkim sukces w edukacji matematycznej? - Kaiser, Izabella (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The work deals with the subject of mathematical education of students with a mild mental disability in the context of their educational success. The author points out at the need of personal success and self-esteemof persons with mental disabilities, taking into account problems connected with fulfilling those needs and the necessity of applying a very individualized perspective in measuring each person’s success. Difficulties in learning mathematics experienced by students of special schools have been discussed, and suggestions for methods of teaching mathematics have been presented that are expected to ensure the required educational success. The first method is the functional teaching of mathematics based on the application of active methods in which a student may undertake operational activity moving from the concrete to the mathematical abstract. The second proposal is the Montessori system, in which a child is defined as an individual able to acquire an independent personality and freely develop his or her talents, interests and strong points. On the basis of the author’s own observations conducted at the Special Schools Complex no. 102 in Poznań it has been demonstrated that functional learning and the application of Montessorian materials in teaching mathematics greatly facilitate the efficiency in following the school curriculum, ensuring individual mathematical success for every child.
Keywords: czynnościowe nauczanie matematyki; metoda Montessori; niepełnosprawność intelektualna; sukces edukacyjny